Characterization of soybean genotypes for Asian soybean rust reaction under screen house condition - ALFI INAYATI; ERIYANTO YUSNAWAN (Biodiversitas Journal of Biological Diversity, 2016)
Inayati A, Yusnawan E. 2016. Characterization of soybean genotypes for Asian soybean rust reaction under screen house condition. Biodiversitas 17: 609-613. Asian soybean rust (ASR) caused by Phakopsora pachyrhizi is one of the major diseases limiting soybean yield. This disease has widely spread on soybean crops in Indonesia. The use of resistant cultivars is one of the economical approaches to control ASR. The objectives of this study were to assess the resistance of soybean lines derived from crossing two largeseeded cultivars (Baluran and Grobogan) with a broad adaptive cultivar (Kaba) and to identify resistant genotype characteristics under screen house conditions. All genotypes were artificially inoculated with P. pachyrhizi uredospores. Number of pustules per leaf, the development of ASR, and yield components including number of intact pods per plant, number of empty pods, and weight of pods per plant were observed. Thirteen lines of Baluran pedigrees had higher resistant response to ASR compared to Grobogan pedigrees. Fewer numbers of pustules (8 pustules cm-2), lower value of area under the disease progress curve (AUDPC), and redish brown (RB) lesion type were observed in resistant lines. In contrast, susceptible lines had more pustules (> 21 pustules cm-2), higher AUDPC value, and had mixed lesion type (RB and Tan). ASR reduced seed size and yield. The average weight of 100 seeds of resistant lines was 10.2 g while on susceptible lines, the 100-seed weight ranged from 8.7 to 12.6 g. The average yield per plant varied from 2.7 to 6.1 g.Baluran/Grobogan pedigrees were more susceptible to ASR than Baluran/Kaba pedigrees, however, those pedigrees showed better yield per plant and were supposedly more tolerant to ASR.